A Multivariate Analysis of Selected Variables of Manufacturing Business Enterprises - Goronzy, Friedheim (Academy of Management Journal, 1968)
The behavior of business organizations is influenced by many interrelated qualitative and quantitative factors.The simultaneous interaction of these factors present many problems for a scientific inquiry.Testing of univariate hypotheses under application of the ceteris paribus clause does not appear to be the appropriate research approach to such complex situations.Rather, it seems that multivariate phenomena should be analyzed with multivariate research tools.Such a multivariate analysis on 50 business organi zations has been performed in this study.Empirically derived multivariate hypotheses are scarce in organizational research.Therefore, this study was performed to search for such multivariate hypotheses on the basis of a selected number of characteristics or variables of industrial organizations.The sample of 50 firms was drawn from machinery manufacturing enterprises classified under the Standard Industrial Classification, 35.The data collected for the selected characteristics were primarily objective accounting-type information.Nine hypotheses were derived through repeated application of factor analysis in xi conjunction with canonical correlation, discriminatory analysis and cluster analysis.The various analyses of* this study in connection with two other research studies reported in the literature indicated the presence of common factors in industrial organizations: size and technology.The influence of these factors was very pervasive and measurably influenced the basic characteristics of the surveyed business enterprises.Therefore, most hypotheses have been stated with reference to these factors.The research indicated also the presence of two specific factors: resource utilization and product strategy.Because of the exploratory nature of this multivariate research, other specific factors found in this investigation were considered in the formulation of hypotheses, but not regarded as truly independent factors or dimensions.The nine hypotheses that emerged from this investi gation are enumerated below: Hypothesis 1, The perceived importance of managerial objectives is influenced by the size of the business enterprise.Hypothesis 2. The span of control of top management increases with the size of the enterprise, reflecting the rising importance of subsidiary activities.Hypothesis 3_.The size of the unit of supervision is independent of the size of the business enterprise, but increases with team-oriented production methods.Hypothesis 4. Division of labor tends to increase with enterprise size and workflow-oriented production methods.Hypothesis J5.The administrative overhead decreases relative to the increasing size of the enterprise.Hypothesis jj.The larger companies and the companies manufacturing high complexity products tend to have a lower asset turnover.Hypothesis ]_.•The technological content of a product influences the customer service orientation of the firm.Hypothesis 8. Direct sales results in greater information feedback for product improvement.Hypothesis £.Sales per employee and sales per production worker increases with enterprise size and the technological complexity of products.The hypotheses and the common factors should be viewed as guides for further research.Although this study indicated the influence of behavioral variables on the xiii characteristics of the organizations, their influence was not explicitly measured.Therefore, further multivariate research should put greater stress on the inclusion of variables indicative of behavioral phenomena.The behavioral variables selected for analysis should also be objective and accounting-type data; e.g., grievances, personnel turnover, and number of suggestions for improvement.Multivariate analysis of organizational performance appears to be a very promising managerial planning and control tool.This writer thinks that periodic multivariate analysis of business operations will become as important and as regular as budgets and other management, reports.xiv CHAPTER I pertinent and relevant is largely a matter of judgment of the researcher and the hypotheses that he has formulated about organizational phenomena.The researcher who views the business organization as a system of structures and functions will select different variables than the researcher who thinks of an enterprise as the interaction of subgroups.The theories of the "classical" organization and management theo rists and those of "behavioral" scientists provide good examples of the contrasting perceptions of researchers.In order to clearly demonstrate the obi ectives and the meaning of this research study, a short summary of the major di mensions of organization theory as seen by classical and behavioral students of organization appears to be in order at this point.This brief outline of organization theory may be viewed as a concise review of the pertinent literature.